2021
DOI: 10.3389/fphar.2020.613160
|View full text |Cite
|
Sign up to set email alerts
|

Bazedoxifene Regulates Th17 Immune Response to Ameliorate Experimental Autoimmune myocarditis via Inhibition of STAT3 Activation

Abstract: Myocarditis is a type of inflammatory cardiomyopathy that has no specific treatment. Accumulating evidence suggests that Th17 cells play a prominent role in the pathogenesis of myocarditis. Interleukin-(IL)-6-mediated signal transducer and activation of transcription 3 (STAT3) signaling is essential for Th17 cell differentiation and secretion of inflammatory cytokines. Bazedoxifene inhibits IL-6/STAT3 signaling in cancer cells, but its effect on the Th17 immune response induced by myocarditis remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In 2019, it was reported that bazedoxifene treatment prevented apoptosis of satellite cells through the estrogen receptor, suggesting a pro-survival effect on muscular cells (Collins et al, 2019). More recently, some studies suggested that bazedoxifene played a role as an inducer of autophagy, on one hand, through PDGF-BB regulation in vascular smooth muscle cells (Song et al, 2020) and, on the other hand, by inducing autophagosome formation and LC3B-II protein expression through Akt/mTOR signaling in macrophages infected with M. tuberculosis (Ouyang et al, 2020) or in polarized Th17 cells (Wang et al, 2020). Because bazedoxifene treatment stimulates LC3B vesicles production in LGMD R2 muscular cells and because LC3-II vesicles might be recruited to the damaged membrane site for membrane resealing process (Corkery et al, 2023), we hypothesized that its widespread protective effect might therefore be linked to this effect on autophagy rather than to the clearance of protein aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, it was reported that bazedoxifene treatment prevented apoptosis of satellite cells through the estrogen receptor, suggesting a pro-survival effect on muscular cells (Collins et al, 2019). More recently, some studies suggested that bazedoxifene played a role as an inducer of autophagy, on one hand, through PDGF-BB regulation in vascular smooth muscle cells (Song et al, 2020) and, on the other hand, by inducing autophagosome formation and LC3B-II protein expression through Akt/mTOR signaling in macrophages infected with M. tuberculosis (Ouyang et al, 2020) or in polarized Th17 cells (Wang et al, 2020). Because bazedoxifene treatment stimulates LC3B vesicles production in LGMD R2 muscular cells and because LC3-II vesicles might be recruited to the damaged membrane site for membrane resealing process (Corkery et al, 2023), we hypothesized that its widespread protective effect might therefore be linked to this effect on autophagy rather than to the clearance of protein aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and fibrosis of the myocardium are two important etiological causes of myocarditis (32). Following an autoimmune attack, a large number of immune cells infiltrate the myocardium, leading to myocardial damage, myocardial structural disintegration and the production of proinflammatory cytokines, such as IL-6, IL-1β and TNF-α (33). This process further exacerbates myocardial damage.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of Th17 cells are elevated in patients with myocarditis. Blocking Th17 cell activity via drugs such as Bazedoxifene ameliorates myocarditis in experimental models [186]. Furthermore, a connection to macrophage activation syndrome is suggested by a study that confirmed that macrophages infiltrated the heart muscle and became activated, releasing toxic cytokines, in association with vaccine-induced myocarditis [187].…”
Section: τγφ-β σιγναλλινγ ανδ τηε δε ελοπμεντ οφ α τη17 ρεσπονσεmentioning
confidence: 99%